Tindak Pidana Berkendara Dalam Keadaan Mabuk Yang Mengakibatkan Kematian (Studi Kasus Putusan No. 61/Pid.Sus/2020/PN.Wgw) - Ramadhandiko, Difqa Alvi; Rivaldi, Chika Aurel; Rahman, Naila Kamila; Rianda, Puja; Fedira, Revania; Yuli W, Yuliana (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The state of intoxication is one of the factors in an accident, namely because someone who is drunk is trying to bring the vehicle in a state of unconsciousness so that the probability of harming others is higher. La Fani is an example of a perpetrator who drove drunk and hit the victim's motorcycle La Jasi. This study examines the decision No. 61/Pid.Sus/2020/Fr.The Wgw deals with the legal consequences of the criminal act of drunk driving to the point of causing the death of another person and links it to the 16th goal of the SDGs . In this study used legal research methods according to the law. Normative law research studies library law by looking at library materials or secondary materials. This method also analyzes various sources of legal information, which are then neatly arranged to make it easier to draw conclusions related to these problems. For the sake of enabling positive regulations and other relevant provisions to be adapted to current problems, legislation is used in this study. After an in-depth study, it was found that La Fani was guilty of operating a motor vehicle while intoxicated and resulting in the taking of the lives of others in accordance with law no. 22 of 2009 on traffic and Road Transport, Article 311 paragraph (5). To meet the 16th Sustainable Development Goal (SDGs), there is a need for strict enforcement of the Law Against Drunk Driving and increased public awareness of the issue of drunk housing in general through educational and social campaigns.